Research of phenolic compound of a horsetail wood (Equisetum sylvaticum L.) - R. A. Bondarchuk; N. E. Kolomiets (Бюллетень сибирской медицины, 2011)
The results of research of phenolic compounds in an elevated part of a horsetail wood, growing in Tomsk and Kirov Regions are presented. The quantitative estimation of flavonoids and phenolic acidsspent of spectrophotometric method. Qualitative structure of phenolic compoundsstudied by chromatography. It is established that the Siberian samples have more various structure flavonoids and phenolic acids. Nine constant substances for samples of a horsetail wood in independence of a growth place are defined.